Mabuk (di) Indonesia : Membongkar Struktur di Balik Fenomena Korban Tewas Karena Oplosan - Rio Heykal Belvage (Umbara, 2017)
Discussing alcohol, many dimensions will likely to involve: social, history, culture, politics, economy and literature. Like rubbing salt into the wounds, the government stakeholders and media use bootleg liquor (oplosan) as a proof to their rational misconception to corner the victims or communities, saying that they have “low awareness of the danger of alcohol.” It seem that they, the government and media, ignore its intricate structures which enable those deadly liquors to flare. This paper, therefore, would like to observe broader picture of the reality of alcohol in a society, focusing on the ignored dimensions of dominant discourse.Keywords : Alcohol, culture, rationality, bootleg liquor (oplosan)